Effectiveness of Interdisciplinary Strategies in Addressing Public Health Challenges: A Quantitative Study - Indra Tri Astuti; Mulyati (Edukasi Ilmiah Indonesia, 2026)
Introduction: Public health challenges are increasingly complex and driven by the interaction of biomedical, social, economic, environmental, and behavioral determinants. Addressing these challenges requires integrated responses that transcend single-discipline approaches. Interdisciplinary strategies have been widely promoted; however, quantitative evidence demonstrating their effectiveness in improving public health outcomes remains limited. This study aimed to quantitatively examine the effectiveness of interdisciplinary strategies in addressing public health challenges and to analyze the relationship between interdisciplinary collaboration and public health program effectiveness. Methods: A quantitative cross-sectional analytical design was employed. The study involved a total population of 50 health professionals and program managers from primary health care centers, hospitals, and public health offices engaged in interdisciplinary public health activities. Data were collected using a structured questionnaire measuring interdisciplinary strategy implementation, including interprofessional communication, shared decision-making, and coordination across disciplines. Public health program effectiveness was assessed through indicators of program performance, service delivery efficiency, and perceived outcome improvement. Data were analyzed using descriptive statistics and Pearson correlation analysis, with statistical significance set at p < 0.05. Results: he findings indicated that the mean scores for all dimensions of interdisciplinary strategies and public health effectiveness were above the midpoint of the scale, reflecting positive implementation levels. Bivariate analysis demonstrated statistically significant positive correlations between interdisciplinary strategy implementation and public health program effectiveness (r = 0.62, p < 0.001). Interprofessional communication and coordination across disciplines showed the strongest associations with public health effectiveness. Conclusion: Interdisciplinary strategies are significantly associated with improved public health program effectiveness. Strengthening structured collaboration, communication, and coordination across disciplines is essential for addressing complex public health challenges and enhancing sustainable public health outcomes